Efeitos das avaliações externas na administração escolar: controle e emancipação da educação básica - Carvalho, Lilian Silva de (Universidade Federal de São Carlos, 2021)
The theme of this dissertation refers to external evaluations, its object was the effects of these evaluations on school administration. The general objective was to analyze the effects of external evaluations on the administration of Brazilian public schools from 2000 to 2019, based on articles published by The Brazilian Journal of Education Policy and Administration - RBPAE. The specific objectives were to configure these effects and to understand their main directions about managerial and/or emancipatory aspects. The investigation was developed within the scope of the Study and Research Group on School Organization: Democracy, Human Rights and Manager Training – DEFORGES. It was a qualitative and documentary investigation, having content analysis as a methodology. The choice for articles published by RBPAE was because school educational administration and educational policies make up, for the most part, its scope. The investigated problem was: How are the effects of external evaluations configured in the administration of Brazilian public schools? The hypothesis was that external evaluations, the result of neoliberal educational policies, have as one of their functions to control and regulate school life, in favor of the implementation of official curricula and the success of schools in terms of performance indicators. Through the analysis carried out, the effects of external evaluations on the administration of public schools were grouped into the following thematic axes: accountability; curriculum adequacy; student learning; possibilities for emancipation; quality of education and teacher regulation. The results allow us to affirm that external evaluations can contribute to the improvement of school administration in an emancipatory perspective. They can lead school teams to rethink their practices, for example, adhering to innovative actions for genuine school inclusion; adapting official curricula according to the specific needs and demands of certain schools, groups and/or students; composing a concept of social quality of education for each school, considering internal and external indicators; seeking equity in the provision and distribution of socially referenced quality education; and, investing in training in and for each school. These courses of action indicate that school administration can be built through the communicative rationality that structures education towards social justice.
Effects of external evaluations on management school: control and emancipation of basic education
Efectos de las evaluaciones externas en la gestión escuela: control y emancipación de la educación básica
Keywords: Avaliações externas; Administração escolar; Controle; Emancipação; External evaluations; School administration; Control; Emancipation; CIENCIAS HUMANAS::EDUCACAO